Thrust moraines and rock glaciers: relationships between subsurface structures and morphodynamics in Swiss glacier forefields dominated by glacier-permafrost interactions - Kunz, Julius; Buchelt, Sebastian; Wiegand, Tim; Ullmann, Tobias; Kneisel, Christof (EGUsphere, 2025)
Abstract. Glacier-permafrost interactions in Alpine environments significantly influence geomorphological processes, making it essential to understand the relationship between subsurface structures and surface morphodynamics for predicting landscape evolution under climate change. So far, the direct correlation between subsurface ice distribution and surface movement for thrust moraine complexes and rock glaciers remains poorly understood. This study investigates the internal structure and morphodynamics of both landform types in two Swiss glacier forefields, aiming to determine how subsurface ice content and structure influence recent surface displacements. We combined electrical resistivity tomography (ERT) with Differential Interferometric Synthetic Aperture Radar (DInSAR) to assess subsurface resistivity and surface displacement patterns. The study focuses on two sites in the Valais region (Swiss Alps), analyzing spatial movement patterns and their correlation with subsurface properties through regression analysis. ERT revealed distinct differences between the ice-rich thrust moraine complexes and the more heterogeneous internal structure of the investigated rock glaciers. DInSAR-derived displacement patterns showed that moraine complexes exhibit predominantly vertical subsidence with high seasonal variability, while rock glaciers display more consistent horizontal movement. Regression analysis confirmed strong correlations between high-resistivity zones and intense surface dynamics in moraine complexes, with the logarithm of maximum resistivity correlating with absolute horizontal displacement (R² = 0.75) and elevation change (R² = 0.76). Instead, rock glaciers exhibited weaker correlations (R2 ≤ 0.3), likely due to heterogeneous internal structures and more complex creep processes, which differ from the subsidence-dominated movements in the ice-rich moraines. These findings underscore the importance of distinguishing between these landform types in permafrost studies and climate change assessments.